Analyzing External Environment Mc Donald’s - Cristina Cristina; Cindy Cindy; Thalia Wang; Dennys Ng; Jeffrey Andelson (Universitas Muhammadiyah Makassar, 2024)
The rapid development and advancement of technology plays a significant role for fast food restaurants. As technology continues to improve, literacy and the dissemination of information about fast food are increasing. The McDonald's company is a restaurant that provides fast food service which is quite good, because from the formation of McDonald's itself, it has implemented operating standards in the form of service and cleanliness of the restaurant. In this research we use The five forces of competition model and PESTEL analyziz. The purpose of this study is to determine the effect of strategic quality on customer satisfaction